2020
DOI: 10.1128/mbio.00363-20
|View full text |Cite
|
Sign up to set email alerts
|

Hfq and sRNA 179 Inhibit Expression of the Pseudomonas aeruginosa cAMP-Vfr and Type III Secretion Regulons

Abstract: Pseudomonas aeruginosa is a Gram-negative opportunistic pathogen causing skin and soft tissue, respiratory, and bloodstream infections. The type III secretion system (T3SS) is one important virulence factor. Production of the T3SS is controlled by ExsA, a transcription factor that activates expression of the entire T3SS regulon. Global regulators including Vfr, RsmA, and Hfq also contribute to regulation of the T3SS. Vfr is a cAMP-responsive transcription factor that activates exsA transcription. RsmA, an RNA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 51 publications
0
24
0
Order By: Relevance
“…(D) Simplified overview of the Gac/Rsm pathway that controls RsmA levels and pertinent parts of its downstream regulon. cytotoxicity in hfq mutants since RsmA is de-repressed in this model (Janssen et al, 2020). Our experiments show that RsmA negatively regulates vfr post-transcriptionally.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…(D) Simplified overview of the Gac/Rsm pathway that controls RsmA levels and pertinent parts of its downstream regulon. cytotoxicity in hfq mutants since RsmA is de-repressed in this model (Janssen et al, 2020). Our experiments show that RsmA negatively regulates vfr post-transcriptionally.…”
Section: Discussionmentioning
confidence: 56%
“…In some previous studies, RsmA was proposed to be a positive regulator of vfr due to decreased cytotoxicity in Δ rsmA mutants ( Marden et al, 2013 ). A subsequent study proposes that Hfq assists sRNAs to inhibit RsmA activity, resulting in increased cytotoxicity in Δ hfq mutants since RsmA is de-repressed in this model ( Janssen et al, 2020 ). Our experiments show that RsmA negatively regulates vfr post-transcriptionally.…”
Section: Discussionmentioning
confidence: 99%
“…Given that RsmY/Z predominantly bind to RsmA/N under the conditions in which CLIP-seq was performed and the effect of SPA0079 is negligible, future studies should be performed using ΔrsmY/Z mutant to determine whether or not the SPA0079 sRNA are indeed RsmA/N antagonist. A recent paper shows that sRNA179 (also annotated as SPA0034) expression stimulates RsmY transcription (64). Additionally, the expression of sRNA179 is activated by QS similar to SPA0079 (35).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that RNase E and Hfq have similar (AU-rich) target sequences that should permit Hfq to protect sRNA from RNase E attack [ 54 ]. In P. aeruginosa , RsmY has been described as stabilized by Hfq, which sequesters RNase E cleavage sites [ 55 ], and thus enhances RsmA sequestration by RsmY [ 56 ]. In P. brassicacearum , an interaction of Hfq with RsmY and RsmZ may explain the extreme stability of these two sRNAs.…”
Section: Discussionmentioning
confidence: 99%